Durvalumab for recurrent or metastatic head and neck squamous cell carcinoma: Results from a single-arm, phase II study in patients with ≥25% tumour cell PD-L1 expression who have progressed on platinum-based chemotherapy. (January 2019) - Zandberg, Dan P.; Algazi, Alain P.; Jimeno, Antonio; Good, James S.; Fayette, Jérôme; Bouganim, Nathaniel; Ready, Neal E.; Clement, Paul M.; Even, Caroline; Jang, Raymond W.; Wong, Stuart; Keilholz, Ulrich; et al.
Abstract: Background: Patients with recurrent/metastatic head and neck squamous cell carcinoma (R/M HNSCC) progressing on platinum-based chemotherapy have poor prognoses and limited therapeutic options. Programmed cell death-1 (PD-1) and its ligand 1 (PD-L1) are frequently upregulated in HNSCC. The international, multi-institutional, single-arm, phase II HAWK study (NCT02207530 ) evaluated durvalumab monotherapy, an anti-PD-L1 monoclonal antibody, in PD-L1-high patients with platinum-refractory R/M HNSCC. Patients and methods: Immunotherapy-naïve patients with confirmed PD-L1-high tumour cell expression (defined as patients with ≥25% of tumour cells expressing PD-L1 [TC ≥ 25%] using the VENTANA PD-L1 [SP263] Assay) received durvalumab 10 mg/kg intravenously every 2 weeks for up to 12 months. The primary end-point was objective response rate; secondary end-points included progression-free survival (PFS) and overall survival (OS). Results: Among evaluable patients (n = 111), objective response rate was 16.2% (95% confidence interval [CI], 9.9–24.4); 29.4% (95% CI, 15.1–47.5) for human papillomavirus (HPV)-positive patients and 10.9% (95% CI, 4.5–21.3) for HPV-negative patients. Median PFS and OS for treated patients (n = 112) was 2.1 months (95% CI, 1.9–3.7) and 7.1 months (95% CI, 4.9–9.9); PFS and OS at 12 months were 14.6% (95% CI, 8.5–22.1) and 33.6% (95% CI, 24.8–42.7). Treatment-related adverse events were 57.1% (any grade) and 8.0% (grade ≥3); none led to death. At data cut-off, 24.1% of patients remained on treatment or in follow-up. Conclusion: Durvalumab demonstrated antitumour activity with acceptable safety in PD-L1-high patients with R/M HNSCC, supporting its ongoing evaluation in phase III trials in first- and second-line settings. In an ad hoc analysis, HPV-positive patients had a numerically higher response rate and survival than HPV-negative patients. Highlights: This study assessed durvalumab in patients with R/M HNSCC and PD-L1-high expression. Patients had failed 1 platinum-based chemotherapeutic regimen in the R/M setting. The ORR for all patients was 16.2% with a median OS of 7.1 months. HPV-positive patients had a numerically higher response rate and longer survival. Durvalumab showed antitumour activity with acceptable safety in the HAWK study.